The Mind in Exile : Thomas Mann in Princeton - Corngold, Stanley (Book collections on Project MUSE., 2022)
"In the years 1938-1941, Princeton was home to an extraordinary constellation of emigre intellectuals-including a particular quartet of thinkers: the novelists Thomas Mann and Hermann Broch, Albert Einstein, and perhaps the least well known of the group, a professor and polymath at the Institute for Advanced Study, Eric Kahler. This book aims to tell the story of their intimate artistic, political, and intellectual activity during the years of Mann's residence in Princeton as a Professor of Humanities at Princeton. The group, who met one another often, mainly at the house of Kahler or Mann, was termed by Charles Greenleaf Bell, a young poet and ardent disciple of Kahler, the "Kahler-Circle." They were fiercely productive scholars. During Mann's residence, he finished his "Goethe-novel" Lotte in Weimar; composed a surrealistic Indian novella The Transposed Heads; and resumed work on the last novel in his epic tetralogy Joseph and His Brothers. He read aloud from these works, while they were in progress, to Kahler and Broch. Kahler in turn discussed his political essays with Mann and was a deeply engaged critic of Mann's fiction; and Mann relied on Kahler, a polymathic intellectual historian and his closest friend, for his political sagacity. Broch, too, read sections of his epic novel The Death of Vergil aloud to Mann and Kahler, his host. Einstein, for all the likeness of his political views with Mann's, preferred the company of Kahler and Broch to that of Mann, whom he termed "an oppressive schoolmaster." To his friends, Einstein was an inspiration, both for his thought and his material support: he also lent Kahler the money to buy the celebrated house at One Evelyn Place and accommodated the impoverished Broch as a house sitter. Kahler at the time was writing what likely be his most widely known book, Man the Measure, which was published two years late in 1943 and for which Einstein wrote the foreword. Corngold aims to tell the story of the story of the intertwined lives and minds of these four great thinkers during their overlapping residence in Princeton during a time of both political and cultural crisis. and culturally pivotal period. He will draw on rich sources for their interactions: Mann's diaries from 1938-1941, foremost, as well as edited volumes of the correspondence of Mann and Kahler, Mann and Broch, and Kahler and Broch. Until now there is no single book that encompasses the precarious but perfervid intellectual life of them all. Corngold will be measuring the extent to which their personal exchanges affected their writings and their political activity"--